Cardiac tamponade as a manifestation of severe dermatomyositis. (23rd September 2016) - Kurth, Benjamin James; Wagler, Vanya; Keith, Michael
Abstract : In connective tissue disorders, the incidence of pericardial disease and pericardial effusion can be up to 58%, and if untreated, it can lead to cardiac tamponade which can be fatal. Physicians must have a high index of suspicion for this disease as diagnosis can be delayed while evaluating more common causes of tachycardia and hypotension in the immunosuppressed (ie, sepsis). We present a 55-year-old woman with a severe case of dermatomyositis, marked by significant weight loss, a bedridden state and hallmark cutaneous findings. On evaluation of interstitial lung disease, a pericardial effusion was incidentally noted. Serial examination revealed increasing fluid accumulation and progressive tachycardia, and diagnosis of cardiac tamponade was made on echocardiography. After initial pericardiocentesis, the effusion rapidly re-accumulated requiring a pericardial window. In severe presentations of rheumatic disease, cardiac tamponade should be considered as a cause of tachycardia, with or without associated hypotension.